2018
DOI: 10.1021/acs.biochem.7b01142
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of N2 Reduction Catalyzed by Fe-Nitrogenase Involves Reductive Elimination of H2

Abstract: Of the three forms of nitrogenase (Mo-nitrogenase, V-nitrogenase, and Fe-nitrogenase), Fe-nitrogenase has the poorest ratio of N reduction relative to H evolution. Recent work on the Mo-nitrogenase has revealed that reductive elimination of two bridging Fe-H-Fe hydrides on the active site FeMo-cofactor to yield H is a key feature in the N reduction mechanism. The N reduction mechanism for the Fe-nitrogenase active site FeFe-cofactor was unknown. Here, we have purified both component proteins of the Fe-nitrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
119
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(128 citation statements)
references
References 54 publications
4
119
0
Order By: Relevance
“…Compared with the Mo-Nase, less is known about the cellular costs of alternative V-and Fe-Nase-based diazotrophy. All Nase isoforms produce H 2 as an obligatory byproduct of N 2 reduction (Simpson and Burris, 1984;Harris et al, 2018a;Harris et al, 2018b). Early in vitro data indicated that the alternative V-and Fe-Nases produce more H 2 than the Mo-Nase, resulting in greater energy and reducing power requirements (Eady, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the Mo-Nase, less is known about the cellular costs of alternative V-and Fe-Nase-based diazotrophy. All Nase isoforms produce H 2 as an obligatory byproduct of N 2 reduction (Simpson and Burris, 1984;Harris et al, 2018a;Harris et al, 2018b). Early in vitro data indicated that the alternative V-and Fe-Nases produce more H 2 than the Mo-Nase, resulting in greater energy and reducing power requirements (Eady, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Further, an ancient Mo‐independent nitrogenase may have been capable of—albeit inefficiently—reducing nitrogen by a cofactor resembling the Fe‐S‐C cluster assembled by NifB, which constitutes the biosynthetic precursor to the FeMo‐cofactor (Boyd & Peters, ; Mus et al, ; Soboh et al, ). Though our sequence analyses cannot fully assess ancestral nitrogenase dependence for a NifB‐cofactor, it is likely that the NifB‐cofactor resembles the structure and composition of the FeFe‐cofactor, excepting homocitrate (Corbett et al, ; Guo et al, ; Harris, Lukoyanov, et al, ). However, the greater similarity of AncC–D active sites to those of Mo‐nitrogenases than Fe‐nitrogenases likely suggests ancestral dependence on a cofactor incorporating Mo rather than only Fe, as would be the case for the NifB‐cofactor.…”
Section: Discussionmentioning
confidence: 99%
“…During catalysis, the electron delivery component transiently associates with and delivers electrons to the catalytic component (Hageman & Burris, ). Electrons accumulate at the active site for N 2 binding and reduction (Hoffman, Lukoyanov, Yang, Dean, & Seefeldt, ), which houses a homocitrate‐metallocluster cofactor unique to each nitrogenase form: the FeMo‐cofactor in Nif (Figure b), FeV‐cofactor in Vnf (Figure c), and FeFe‐cofactor in Anf (Figure d) (Eady, ; Harris, Lukoyanov, et al, ; Krahn et al, ; Mus et al, ; Sippel & Einsle, ; Spatzal et al, ). Available spectral evidence suggests that these cofactors are structurally similar, with the main difference being the substitution of a Mo, V, or additional Fe atom (FeV‐cofactor is also proposed to incorporate a carbonate ligand in place of one sulfur atom; Sippel & Einsle, ) (Eady, ; Krahn et al, ; Spatzal et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations